2015
DOI: 10.1002/ps.4012
|View full text |Cite
|
Sign up to set email alerts
|

Lactones 46. Synthesis, antifeedant and antibacterial activity ofγ-lactones with ap-methoxyphenyl substituent

Abstract: The results of biological tests showed that halogen atom removal significantly increased the antifeedant properties of γ-lactones with a p-methoxyphenyl substituent. Unsaturated lactones are most promising in the context of their possible industrial application as crop protection agents. Further structural modifications of lactones with aromatic rings are needed to find important structural factors increasing the antibacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…Therefore, novel bactericides are needed as alternative control agents. Lactones are well known for their biological activities, including anti‐bacterial activity . PTL is a sesquiterpene lactone well known for its anti‐tumor and anti‐inflammatory activities, and it also has shown inhibitory activities against phytopathogens .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, novel bactericides are needed as alternative control agents. Lactones are well known for their biological activities, including anti‐bacterial activity . PTL is a sesquiterpene lactone well known for its anti‐tumor and anti‐inflammatory activities, and it also has shown inhibitory activities against phytopathogens .…”
Section: Discussionmentioning
confidence: 99%
“…Lactones are well known for their biological activities, including anti-bacterial activity. 27 PTL is a sesquiterpene lactone well known for its anti-tumor and anti-inflammatory activities, and it also has shown inhibitory activities against phytopathogens. [18][19][20] In the preliminary study, we assayed the anti-microbial activities of PTL against 11 plant-pathogenic fungi, three plant-pathogenic oomycetes, wileyonlinelibrary.com/journal/ps and three plant-pathogenic bacteria at 10 mg L −1 in vitro, and found that PTL was most effective against Xoo (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The natural lactones isolated from fruits and essential oils can be used as fragrance components, like jasmine lactone or as a flavor in the food industry (δ-decalactone) [1][2][3]. Those compounds can also be pheromones [4,5] or antifeedants [6][7][8] but the largest interest is put in their antimicrobial and cytotoxic potential. There are numerous examples presenting the antibacterial and antifungal activity of lactones [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Another potential reason for the antimicrobial action observed herein is the presence of non-reacted NHS esters, since lactones are known to have a wide spectrum of antimicrobial effect. 73 To verify this, the antibacterial activity of the NHS-activated P(PF-co-EG) network was also tested, and it was found to exhibit higher biocide action than the neat copolymer (i.e. in the range of 0.60-0.75 and 0.25-0.40 against Gram-negative and Gram-positive bacteria, respectively).…”
Section: Antibacterial Propertiesmentioning
confidence: 99%